Chitosan succinate/PVA-PEG Membrane: Preparation, Characterization and Permeation Ability Test on Creatinine - Sri Juari Santosa; Retno Ariadi Lusiana; Vivi Dia Ahmad Sangkota (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2018)
Evaluation character of chitosan membrane-succinate / poly vinyl alcohol-poly ethylene glycol (PVA-PEG) were prepared in acetic acid solvent through a phase inversion method has been performed. The study began with the preparation of crosslinked chitosan compounds with succinic acid, followed by preparation into membrane by combining PVA-PEG. Character analysis of the resulting material using FTIR, EDX, TGA, water absorption test, tensile strength, membrane hydrophilicity. The ability of membrane permeation was tested against creatinine. The results showed that the succinate had reacted with chitosan. Chitosan modification through cross link and polymer alloys increases tensile strength and membrane strain of 1.7-2.5 x of pure chitosan membrane. In addition, the modified membrane also has higher water absorption and hydrophilicity values than the unmodified membrane, and this implies the ability of membrane-induced creatinine permeation. Permeable permeation values were 13.8% in chitosan, 24.84% on chitosan-succinate and 25% in chitosan-succinate / PVA-PEG. Chitosan-succinate membranes have the ability to use more than 4x repeated use.